The Effect of Addition Boster Manstap to Density Cell of Chlorella sp - Silvia Delilla; Syafriadiman Syafriadiman; Saberina Hasibuan (Jurnal Perikanan dan Kelautan, 2022)
This research was conducted in August – September 2020, at the Quality of Aquaculture Laboratory, Fisheries and Marine Faculty, Riau University. The purposed of this study was to see the effect of addition booster manstap to density cell of Chlorella sp. and the best dose for cultures of Chlorella sp. The research uses a completely randomized design (CRD) with one factor, four treatments, and three replications. The treatment in this study was the use of different booster manstap doses (BMD), namely P0 (control), P1 (25 ppm BMD), P2 (30 ppm BMD) and P3 (35 ppm BMD). The result of this research showed the best treatment is P3 (35 ppm BMD) with a cell density of 1176,67 x 104 cells/ml, a specific growth rate of 0,25/day and the highest peak density occurred on day 6. The quality of water value at the time of the research was temperature 29-330C, pH 7-8,3, DO 6,6-7,9 ppm, nitrat 1,5-12,7 mg/L dan posfat 1,70-5,91 mg/L. The quality of water value was good for cultures of Chlorella sp